Effectiveness of Organizational Communication in the Global Age - Udeoba, Adaonye A. (Richtmann Publishing, 2012)
Communication is not a reaction to something, not an interaction with something but a transaction inwhich man invents and attributes meaning to realize his purpose. It should be stressed that meaning issomething invented, assigned and given rather than something received. It is the production of meaningrather than the production of messages that identifies communication. Organizational communication istherefore the flow of materials, information, perceptions, and understanding among the various parts andmembers of an organization. In an organization, a lot of consideration is made on the lines ofcommunications, strategies to be used, technological facilities provided and the communicator shouldknow and understand the different ways with which to communicate with the people in and outside theorganization to effectively achieve their goals. kazt and kahn (1966,p.12) found out that managers in anlisted oral communication and listening as the most important skill for gaining employment and improveworking relationship and even any kind of relationship requires open and accurate lines of communicationand only when such lines exist will one feel free to voice out important feelings and thoughts. This paperfocuses on how effective organizational communication is in this global economic age.